Strategi Guru Pendidikan Agama Islam dalam Mengembangkan Sikap Spiritual Siswa Kelas VII SMP Negeri 6 Palembang - Inne Aprinda; Amilda Amilda; Mardiah Astuti (Bahasa Indonesia, Bahasa English, 2020)
The research aims to describe and analyze the PAI teacher's strategy in developing the spiritual attitude of Grade VII students of SMPN 6, and the factors that influence the PAI teacher's strategy in developing the spiritual attitude of VII students of SMPN 6 Palembang. The results of the study show that, (1) develop the spiritual attitude of VII grade students of SMP Negeri 6 Palembang, namely through the habit of praying after the 0th hour, habituation of the Duha and Dhuhr prayer in congregation, then through teacher guidance to students by giving advice or motivation, by teacher modeling, and approaching through methodsexemplary story (2) Factors supporting the PAI teacher's strategy in developing the spiritual attitude of VII grade students of SMP Negeri 6 Palembang are the existence of creative teachers, the hard work of teachers in motivating students to have good morals, the existence of school programs that support the development of spiritual attitudes of students, the existence of work the same is good between the principal d ith the teacher in the school, the existence of an adequate mosque to carry out worship, the collaboration between parents of students and teachers. While the inhibiting factors are lack of awareness and motivation in students, and lack of supervision from parents in matters of worship.